The Effect of Increasing Customer Purchase Intention in E-Commerce - Sutinem Sutinem; Zindny Kafa Perdana; Abdul Rossi; Muhamad Imam Syairozi; Sani Rusmawati (Sean Institute, 2026)
Customer purchase intention refers to a consumer's tendency to purchase or own a particular product or service. This study aims to determine the effects of Content Marketing, Live Streaming, and the Free Shipping Program on Customer Purchase Intention in Shopee e-commerce. The study employed a quantitative method. The population consisted of all students at Universitas Islam Lamongan. Data were collected through a questionnaire, with a sample of 98 respondents. The data were analyzed using SPSS version 25. The analytical techniques included multiple linear regression, classical assumption tests, t-tests, F-tests, and the coefficient of determination; the questionnaire data were first tested for validity and reliability. Based on the analysis and discussion, the three independent variables—Content Marketing, Live Streaming, and Free Shipping—each had a significant partial effect on Customer Purchase Intention. The resulting multiple linear regression equation was Y = 3.708 + 0.160X1 + 0.285X2 + 0.198X3 + e. At a significance level of 5% or 0.05, the calculated F-value was 104.317, which was greater than the F-table value of 2.70, and the significance value was 0.001, which was less than 0.05. This means that Content Marketing (X1), Live Streaming (X2), and the Free Shipping Program (X3) simultaneously influenced Customer Purchase Intention (Y).